Alleviating effect of quercetin on cadmium-induced oxidative damage and apoptosis by activating the Nrf2-keap1 pathway in BRL-3A cells - Wang, Jicang; Wang, Ke; Ding, Lulu; Zhao, Pengli; Zhang, Cai; Wang, Hongwei; Yang, Zijun; Liu, Zongping (Frontiers in Pharmacology, 2022)
Cadmium (Cd) is a toxic heavy metal extensively used in industrial and agricultural production. Among the main mechanisms of Cd-induced liver damage is oxidative stress. Quercetin (QE) is a natural antioxidant. Herein, the protective effect of QE on Cd-induced hepatocyte injury was investigated. BRL-3A cells were treated with 12.5 μmol/L CdCl2 and/or 5 μmol/L QE for 24 h. The cells and medium supernatant were collected, and the ALT, AST, and LDH contents of the medium supernatant were detected. The activities or contents of SOD, CAT, GSH, and MDA in cells were determined. Intracellular ROS levels were examined by flow cytometry. Apoptosis rate and mitochondrial-membrane potential (ΔΨm) were detected by Hoechst 33258 and JC-1 methods, respectively. The mRNA and protein expression levels of Nrf2, NQO1, Keap1, CytC, caspase-9, caspase-3, Bax, and Bcl-2 were determined by real-time PCR (RT-PCR) and Western blot methods. Results showed that Cd exposure injured BRL-3A cells, the activity of antioxidant enzymes decreased and the cell ROS level increased, whereas the ΔΨm decreased, and the expression of apoptotic genes increased. Cd inhibited the Nrf2-Keap1 pathway, decreased Nrf2 and NQO1, or increased Keap1 mRNA and protein expression. Through the combined action of Cd and QE, QE activated the Nrf2-Keap1 pathway. Consequently, antioxidant-enzyme activity decreased, cellular ROS level decreased, ΔΨm increased, Cd-induced BRL-3A cell damage was alleviated, and cell apoptosis was inhibited. After the combined action of QE and Cd, Nrf2 and NQO1 mRNA and protein expression increased, Keap1 mRNA and protein expression decreased. Therefore, QE exerted an antioxidant effect by activating the Nrf2-Keap1 pathway in BRL-3A cells.